Behaviour of some garlic cultivars planted in June in Santa Catarina, Brazil - Mueller, Siegfried; Biasi, José; Sobrinho, João Alves de Menezes; Muller, Juarez José Vanni (Pesquisa Agropecuaria Brasileira, 2014)
Field experiments were carried out at Curitibanos, SC, Brazil, from 1979 to 1982 to test the behaviour of seventeen garlic cultivars as to productivity and quality for recommendation of some of them for planting in the Planalto Catarinense is June. The following cultivars were tested: Amarante, Branco Mineiro, Cajuru, Caturra, Centenário, Chinês, Roxo Pérola de Caçador, Chonan, Dourados, Gigante de Inconfidentes, Gigante Roxo, Gigante Roxão, Juréia, Gigante de Lavínia, Peruano and Seleção Brasilia 1. Significant correlation was found between yield and plant size measured at 45 (r = 0.641) and at 120 (r = 0.644) days after planting. Cultivar Roxo Pérola de Caçador (7,002 kg/ha) presented the highest yield. Cultivar Peruano (6,117 kg/ha) was the second best, and kept best is storage. However cultivar Peruano presents open bulbs (without the bulb cuticles), being thereafter of industrial type. Cultivar Gigante de Inconfidentes (5,611 kg/ha) and Gigante de Lavínia (5,442 kg/ha) were the third best is yield. However their yields are usually higher when they are planted earlier is the season; this demonstrates that they must be planted earlier, from March to May in this region